The lectin‐like domain of thrombomodulin is a drug candidate for both prophylaxis and treatment of liver ischemia and reperfusion injury in mice. Issue 2 (24th September 2020) - Kawasoe, Junya; Uchida, Yoichiro; Miyauchi, Tomoyuki; Kadono, Kentaro; Hirao, Hirofumi; Saga, Kenichi; Watanabe, Takeshi; Ueda, Shugo; Terajima, Hiroaki; Uemoto, Shinji
Abstract : Ischemia and reperfusion injury (IRI) can occur in any tissue or organ. With respect to liver transplantation, the liver grafts from donors by definition experience transient ischemia and subsequent blood reflow. IRI is a problem not only in organ transplantation but also in cases of thrombosis or circulatory disorders such as mesenteric ischemia, myocardial, or cerebral infarction. We have reported that recombinant human soluble thrombomodulin (rTM), which is currently used in Japan to treat disseminated intravascular coagulation (DIC), has a protective effect and suppresses liver IRI in mice. However, rTM may not be fully safe to use in humans because of its inherent anticoagulant activity. In the present study, we used a mouse liver IRI model to explore the possibility that the isolated lectin‐like domain of rTM (rTMD1), which has no anticoagulant activity, could be effective as a therapeutic modality for IRI. Our results indicated that rTMD1 could suppress ischemia and reperfusion‐induced liver damage in a dose‐dependent manner without concern of associated hemorrhage. Surprisingly, rTMD1 suppressed the liver damage even after IR insult had occurred. Taken together, we conclude that rTMD1 may be a candidate drug for prevention of and therapy for human liver IRI without the possible risk of hemorrhage. Abstract : The lectin‐like domain of thrombomodulin suppresses liver ischemia and reperfusion injury in mice via inhibition of the high‐mobility group box 1 / Toll‐like receptor 4 pathway, even after the insult has started.